Analysis and modeling of COVID-19 epidemic dynamics in Saudi Arabia using SIR-PSO and machine learning approaches - Rafat Zrieq; Sahbi Boubaker; Souad Kamel; Mohamed Alzain; Fahad D. Algahtani (Journal of Infection in Developing Countries)
Introduction: COVID-19 has become a global concern because it has extensive damage to health, social and economic systems worldwide. Consequently, there is an urgent need to develop tools to understand, analyze, monitor and control further outbreaks of the disease.